Field study on routine procedures for navel care in neonatal calves on dairy farms in Eastern Germany - Kim Kristin Meier; Kerstin-Elisabeth Müller; Roswitha Merle; Heidi Arndt; Linda Dachrodt; Martina Hoedemaker; Laura Kellermann; Gabriela Knubben-Schweizer; Maria Volkmann; Annegret Stock (PLoS ONE, 2025)
Clean conditions and prophylactic measures around calving are essential for the health and welfare of calves. Therefore, the objective of this study was to evaluate the association of different navel care (NC) practices on the occurrence of omphalitis in neonatal dairy calves. Between December 2016 and July 2019, 196 dairy farms in Eastern Germany were visited once within a large-scale cross-sectional study. 1,967 calves aged five to 21 days were clinically examined, including palpation of the external umbilicus for inflammation signs. Furthermore, information on animal health and farm management, including the implementation of NC, was obtained through interviews with the farm or herd manager. Causal diagrams were drawn, containing variables considering NC (practice of NC, method of application, preparation applied, frequency of NC, time of first NC, wearing gloves during NC) as influence variables, omphalitis as target variable, and all potential confounders to perform multivariable statistical analyses at animal level. Over one-fourth of all calves examined showed omphalitis signs (n = 525 calves, 26.7%). The odds of omphalitis tended to increase (OR = 2.3) if no NC was performed compared to regular NC. Almost half of all other variables analysed seemed relevant for the occurrence of omphalitis. Administering the preparation into the umbilical cord reduced the odds of omphalitis by 62% compared to no NC. Repeated applications tended to decrease the odds of omphalitis by 44% compared to single applications. Furthermore, wearing gloves during NC tended to increase the odds of omphalitis by 30% compared to not wearing gloves. Neither the preparation applied, the method of application, nor the timing of NC had an impact on the omphalitis occurrence. Considering these results, different NC practices influence the odds of omphalitis in neonatal dairy calves. Nevertheless, further investigations are necessary regarding the application procedure of NC during the daily farm routine.